Dosimetric verification in water of a Monte Carlo treatment planning tool for proton, helium, carbon and oxygen ion beams at the Heidelberg Ion Beam Therapy Center. (31st July 2017) - Tessonnier, T; Böhlen, T T; Ceruti, F; Ferrari, A; Sala, P; Brons, S; Haberer, T; Debus, J; Parodi, K; Mairani, A
Abstract: The introduction of 'new' ion species in particle therapy needs to be supported by a thorough assessment of their dosimetric properties and by treatment planning comparisons with clinically used proton and carbon ion beams. In addition to the latter two ions, helium and oxygen ion beams are foreseen at the Heidelberg Ion Beam Therapy Center (HIT) as potential assets for improving clinical outcomes in the near future. We present in this study a dosimetric validation of a FLUKA-based Monte Carlo treatment planning tool (MCTP) for protons, helium, carbon and oxygen ions for spread-out Bragg peaks in water. The comparisons between the ions show the dosimetric advantages of helium and heavier ion beams in terms of their distal and lateral fall-offs with respect to protons, reducing the lateral size of the region receiving 50% of the planned dose up to 12 mm. However, carbon and oxygen ions showed significant doses beyond the target due to the higher fragmentation tail compared to lighter ions (p and He), up to 25%. The Monte Carlo predictions were found to be in excellent geometrical agreement with the measurements, with deviations below 1 mm for all parameters investigated such as target and lateral size as well as distal fall-offs. Measured and simulated absolute dose values agreed within about 2.5% on the overall dose distributions. The MCTP tool, which supports the usage of multiple state-of-the-art relative biological effectiveness models, will provide a solid engine for treatment planning comparisons at HIT.